2021
DOI: 10.1080/02640414.2021.1929009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of simulated hip muscle weakness on hip joint forces during deep squatting

Abstract: This study aimed to determine the effects of simulated hip muscle weakness on changes in hip joint forces during deep squat motion. Ten healthy individuals performed squat motion at three different positions (0° foot angle [N-squat], 10° toe-in [IN-squat], and 30° toe-out [OUT-squat]). A scaled musculoskeletal model for each participant was used to calculate the muscle and hip joint forces. For each hip muscle, models of full strength, mild muscle weakness (15% decrease), and severe muscle weakness (30% decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Weakness of gluteal muscles might alter the magnitude and direction of JRFs of the hip due to compensatory mechanisms, specifically an increase of muscle forces in other synergistic muscles 46 . Tateuchi et al 9 using individualized, scaled musculoskeletal models of 10 healthy volunteers, simulated mild (15%) and severe (30%) muscle weakness during squats and reported an increase of the anterior hip JRF by 18.3% during a severe weakness of the inferior gluteus maximus and 27.8% during a severe weakness of inferior gluteus maximus/deep external rotators of the hip, due to compensatory increase in quadriceps, hamstrings, and superior gluteus maximus, whereas the medial hip JRF decreased in the inferior gluteus maximus/deep external rotators weakness model. In this study, no change of the hip JRFs in AP and ML direction was observed, but a decrease of the superior JRF following SGN and IGN block in the affected hip and superior overloading of the contralateral unaffected hip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weakness of gluteal muscles might alter the magnitude and direction of JRFs of the hip due to compensatory mechanisms, specifically an increase of muscle forces in other synergistic muscles 46 . Tateuchi et al 9 using individualized, scaled musculoskeletal models of 10 healthy volunteers, simulated mild (15%) and severe (30%) muscle weakness during squats and reported an increase of the anterior hip JRF by 18.3% during a severe weakness of the inferior gluteus maximus and 27.8% during a severe weakness of inferior gluteus maximus/deep external rotators of the hip, due to compensatory increase in quadriceps, hamstrings, and superior gluteus maximus, whereas the medial hip JRF decreased in the inferior gluteus maximus/deep external rotators weakness model. In this study, no change of the hip JRFs in AP and ML direction was observed, but a decrease of the superior JRF following SGN and IGN block in the affected hip and superior overloading of the contralateral unaffected hip.…”
Section: Discussionmentioning
confidence: 99%
“…7 Incorrect squatting execution could induce increased compressive and shear forces at the hip, knee, and ankle joints. 7,8 Several conditions such as chronic hip muscle weakness/ insufficiency, 9 fatigue, 10 pain, 11 and osteoarthritis 12 might influence squat performance 13 and therefore, should be considered when assessing and training patients with these pathologies. In the presence of lower extremity muscle weakness, abnormal movements, and compensation mechanisms might be observed in an attempt to complete the task.…”
Section: Introductionmentioning
confidence: 99%
“…Maximized strengthening of both internal and external rotator muscle groups is important in the homeostasis of the hip, with particular research supporting the deep external rotators, although a specific ratio has not been confirmed. Tateuchi et al 61 showed increased anterior hip joint forces in the deep squat when weakness in the deep external rotators was present. Meinders and colleagues showed that maximal activation of the deep external rotators resulted in decreased hip contact force angles and reduced acetabular loading.…”
Section: Phase Iii: Strengtheningmentioning
confidence: 98%